Room Temperature Reduction of Nitroaromatics Using Pd Nanoparticles Stabilized on Nano‐CeO2. Issue 32 (14th November 2017) - Saikia, Himadri; Borah, Biraj Jyoti; Bharali, Pankaj
Abstract: Palladium nanoparticles stabilized on mesoporous cerium oxide nanoparticles catalyze the reduction of substituted nitroaromatics in presence of sodium borohydride as reductant. A modified two‐step methodology was developed for the synthesis of Pd/CeO2 nanoparticles. First the support CeO2 was synthesized by conventional precipitation method using ammonium oxalate as precipitant and Pd/CeO2 nanoparticles were prepared by hydrothermal treatment. The nanoparticles exhibit excellent catalytic activity and chemoselectivity for the reduction of nitroaromatics towards corresponding amine derivatives at room temperature. A kinetic study suggests that the reaction follows pseudo‐first order rate equation. Thus, synthesized catalyst represents significant role for the reduction of nitroaromatic compounds to value added amino compounds. Abstract : We report a simple and efficient chemical route to synthesize Pd nanoparticles stabilized on nano‐CeO2 which exhibit high catalytic activity for the reduction of nitroaromatics at room temperature.